Association between social support and mutual-support needs among the rural adults in China: a cross-sectional study - Tang, Xi; Li, Ling; Yao, Keru; Luo, Qin; Zhao, Lu; Li, Lu; Wang, Zhihan; Fang, Yijie; Huang, Li; Yin, Xinhong (Frontiers in Public Health, 2023)
Background: In rural China, there is now a huge gap between the supply and demand for old-age care. To close the gap, developing rural mutual old-age services is extremely important. The purpose of this study is to clarify the relationship among social support, mutual support need, and mutual support willingness. Methods: We conducted an online questionnaire survey using a Chinese Internet research company; 2,102 valid responses were received. The measures comprised the Social Support Rating Scale, the Mutual Support Willingness Questionnaire, and the Mutual Support Needs Scale. We calculated Pearson correlations to explore the association of social support with mutual-support need and mutual-support-need willingness. Multivariate analyses were also conducted using these factors as dependent variables. Results: The total score for the mutual support need for the elderly in rural areas was 58.0 ± 12.1 and 36.96 ± 6.40 for social support, approximately 86.8% of the participants were willing to participate in mutual support. Furthermore, mutual support needs were positively correlated with subjective support (p<0.01) and support utilization (p<0.01), but negatively correlated with willingness to support each other (p<0.05). The need for mutual support was also associated with age, education level, dissatisfaction with the current economic situation, health status, and so on. Conclusions: It is necessary for government and health care providers to assess the different needs of rural older people and encourage individuals and organizations to provide mutual support for older people, especially to enhance emotional care for older people and improve their use of support. This is of great significance for developing mutual support services in rural China.